The marquesa eaudiobook Heroines of the golden west series, book 2. - Bly, Stephen (Heroines of the Golden West, 2015)
Isabel Leon, the Marquesa, is an actress who has appeared in performances across the country, yet now she finds herself living in the small western town of Cantrell, Montana. With the town booming, the Marquesa decides it needs a grand hotel. It will take the help, and the heart, of a handsome stranger to make her dream a reality. As their relationship grows, the Marquesa finds her faith getting stronger, too. Soon, she is thinking of a role she has never played before: that of a Christian wife and mother. Linda Stephens' lovely narration perfectly conveys the transformations in the Marquesa's heart and soul.